The Oldest Representative of the Rove Beetle Tribe Pinophilini (Coleoptera: Staphylinidae: Paederinae), from Upper Cretaceous Burmese Amber - Josh Jenkins Shaw; Bo Wang; Ming Bai; Dagmara Żyła (Insects, 2020)
The recently reviewed subtribe Procirrina comprises eight extant genera with a predominately (sub)tropical distribution. Previous phylogenies consistently recover the tribe Pinophilini of the subfamily Paederinae monophyletic. No fossils of the tribe have been described, although compression fossils are known from the Cenozoic Green River Formation (50.3−46.2 Ma) as well as inclusions from the Miocene Dominican (20.43−13.65 Ma) and Mexican (20−15 Ma) ambers. Here we describe †Cretoprocirrus trichotos Jenkins Shaw and Żyła gen. et sp. n., the oldest fossil representative of the tribe Pinophilini, from Upper Cretaceous Burmese amber (ca. 99 Ma). Phylogenetic analyses of morphological data allow its unambiguous placement in the subtribe Procirrina. †Cretoprocirrus trichotos is the second genus of Paederinae described from Burmese amber and provides an important insight into the evolution of the subfamily.